CONTRIBUTION TO DEVELOPING TECHNICAL CREATIVE ACTIVITY OF STUDENTS OF SPECIALIZED TECHNICAL SUBJECTS - HAVELKA, Martin; SERAFIN, Cestmir; KROPAC, Jiri (Trends in education, 2012)
This paper deals with the problems of supporting the development of technical creative activity of students within the technical subjects carrying out the teaching using the students' laboratory experiment. In order to project and carry out such type of teaching, the teacher needs to be able to possess a number of specialized competences important to introduce and control such educational process. This is a part of the subject Special Didactic Practicall Class.
Keywords: laboratory experiment; technical creative activity; teacher's competence to introduce and control the given activites; construction kit Lego Mindstorms; application of the set TETRIX Education Base Set; application of elements of automation.